2016
DOI: 10.1111/are.13080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐level dietary microalgae supplementation on the distal intestinal microbiome of farmed rainbow trout Oncorhynchus mykiss (Walbaum)

Abstract: This is the peer reviewed version of the following article: Lyons, P. P., Turnbull, J. In this study, high throughput 16S rRNA sequencing was used to investigate the effect of a 171Samples were allowed to settle, and total genomic DNA was extracted and purified using the 192Illumina libraries were prepared following the method described by Caporaso, Lauber, Walters, All fish consumed both diets readily and upon conclusion of the trial, the weighed individuals 273 from the treatment group had a higher mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 65 publications
(97 reference statements)
12
67
0
Order By: Relevance
“…Similar prevalence levels were observed in intestinal contents from channel catfish, largemouth bass and bluegill (Larsen, Mohammed, & Arias, ). Although such overwhelming prevalence of Cetobacterium has not been already reported in rainbow trout, the genus appeared common in trout intestine (Etyemez & Balcazar, ; Kim et al., ; Lyons, Turnbull, Dawson, & Crumlish, ; Lyons et al., ). The most prevalent OTU in the present data was close to Cetobacterium somerae, a possible provider of vitamin B 12 for the host (Tsuchiya et al., ; strains previously classified as Bacteroides type A by Sugita, Miyajima, & Deguchi, ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar prevalence levels were observed in intestinal contents from channel catfish, largemouth bass and bluegill (Larsen, Mohammed, & Arias, ). Although such overwhelming prevalence of Cetobacterium has not been already reported in rainbow trout, the genus appeared common in trout intestine (Etyemez & Balcazar, ; Kim et al., ; Lyons, Turnbull, Dawson, & Crumlish, ; Lyons et al., ). The most prevalent OTU in the present data was close to Cetobacterium somerae, a possible provider of vitamin B 12 for the host (Tsuchiya et al., ; strains previously classified as Bacteroides type A by Sugita, Miyajima, & Deguchi, ).…”
Section: Discussionmentioning
confidence: 94%
“…Most studies showed that the bacterial communities in the intestine of rainbow trout changed significantly, depending on the diet with or without plant protein sources as partial substitute for fish meal (Desai et al., ; Heikkinen et al., ; Ingerslev, Strube et al., ; Ingerslev, von Gersdorff Jorgensen et al., ; Mansfield et al., ; Merrifield, Dimitroglou, Bradley, Baker, & Davies, ; Navarrete et al., ; Wong et al., ). The replacement of fish oil by plant oils may also influence gut microbiota (Ingerslev, Strube et al., ; Ingerslev, von Gersdorff Jorgensen et al., ; Lyons, Turnbull, Dawson, & Crumlish, ; Navarrete et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased bacterial diversity in the gut has been found in another single‐celled protein study that fed low inclusion of micro‐algae to rainbow trout kept at 14°C (Lyons et al . ). In contrast, another study found no effect of feeding S. cerevisiae on gut bacterial diversity of rainbow trout, although the yeast was inactivated and the fish were reared at 13°C (Huyben et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Lyons et al . ). More research is needed to determine the nature of Mycoplasma in the fish gut, especially since it represents a high proportion of the microbiota.…”
Section: Discussionmentioning
confidence: 97%
“…; Lyons et al . ). Besides, microalgae positively stimulate gut health possibly by altering immunological responses of fish intestinal tissues, perhaps through modulating the nutrient absorption and/or resistance to pathogens (Katerina ; Kousoulaki et al .…”
Section: Chlorella Vulgaris and Fish Gut Microbiotamentioning
confidence: 97%